PRESENTATION AND MANAGEMENT OF PATIENTS WITH OBSTETRICAL AND GYNECOLOGICAL COMPLICATIONS IN THE DEPARTMENT OF SURGERY - Hadi, Ain Ul; Faridoon, Shehla; Shah, Farrukh Ozair; Raza, Tilal Ahmed; Shah, Muhammad; Aslam, Rashid; Khan, Shehzad Akbar (Journal of Postgraduate Medical Institute, 2021)
Objective: To find out the types of obstetrical and gynecological complications and their subsequent treatment in the department of general surgery. Methodology: This cross sectional study was conducted on 56 patients who presented to department of surgery, Hayatabad Medical Complex, Peshawar from July 2016 to June 2019. Patients presented either as emergency cases with 24-48 hours following surgery or those who were referred to OPD 48 hours after the procedure. Emergency cases included postoperative complications during obstetrical and gynaecological procedures performed in the department of Obstetrics and Gynaecology of the same hospital, and those referred from peripheral hospitals. These emergencies were managed immediately while cold cases were operated on elective operation list. Patients were followed up in the OPD. Data was analyzed with SPSS version 20. Results: Out of 56, 24 (42.8%) cases presented to accident and emergency department while 32 (57.2%) were referred to outdoor department (OPD). The initial surgeries, during which complications occurred, included total abdominal hysterectomy (n=34, 64.3%) followed by, pelvic mass excision (n=8, 14.3%) and cesarean section (n=8, 10.7%). The most common complication was wound infection (n=13, 23.2%) followed by haemorrhage (n=9, 16.1%) and incisional hernia (n=8, 14%). Debridement and dressing (n=13, 23.2%), haemostasis (n=9, 16.1%) and mesh repair (n=8, 14.3%) for incision hernia were the common operative procedures. There was no mortality in emergency as well as cold cases. Conclusion: Total abdominal hysterectomy, cesarean section and vaginal hysrerectomy, being commonly performed procedures, are associated with high percentage of post operative complications.